Lipid profile adjustments may contribute to warming acclimation and to heat impact mitigation by elevated [CO2] in Coffea spp - Scotti-Campos, Paula (2019)
An unexpected heat resilience, and the mitigation of heat impacts by elevated [CO2] were recently reported in Coffea spp. Plants must maintain membrane fluidity and integrity to cope with temperature changes, which requires an adequate lipid dynamics. This work provides the lipid profile (galactolipids, GL; phospholipids, PL; sulfolipids, SL) of chloroplast membranes, and the expression of a set of genes related to lipid metabolism in Coffea arabica L. (cv. Icatu and IPR108) and C. canephora cv. Conilon CL153, under elevated [CO2] (380 or 700 μL L−1), heat (25/20, 31/25, 37/30 and 42/34 °C, day/night) and their interaction. Major membrane lipids alterations, different among genotypes, included: A) responsiveness of total fatty acids (TFAs) synthesis to [CO2] (except IPR108) and heat (except CL153); stronger remodeling (unsaturation degree) in the 700-plants from 37/30 °C to 42/34 °C, coordinated at transcriptional level with the down-regulation of fatty acid desaturase FAD3 gene (C. arabica) and up-regulation of lipoxygenase genes LOX5A (CL153 and Icatu) and LOX5B (Icatu) at the highest temperature; B) quantitative and qualitative modifications in GL (monogalactosyldiacylglycerol, MGDG; digalactosyldiacylglycerol, DGDG), PL (phosphatidylcholine, PC; phosphatidylglycerol, PG), and SL (sulfoquinovosyldiacylglycerol, SQDG) classes, prompted by heat, elevated [CO2], and, especially, the interaction, in CL153 and Icatu. Overall membrane enrichment with MGDG and DGDG as a result of heat and [CO2] interaction in these genotypes, but at the highest temperature only in Icatu the high [CO2] maintained greater contents and unsaturation values of these GLs than in the 380-plants. C) Among PL classes, PG seems to play an active role in heat acclimation of C. arabica genotypes, increasing in 700-plants at 42/34 °C. Globally, Icatu often showed changes closer to those of heat tolerant cv. CL153 than to cv. IPR108. Overall, lipid profile adjustments in chloroplast membranes, from TFAs bulk until FA unsaturation within each class, are expected to contribute to long-term acclimation to climate changes in coffee plant.